2021
DOI: 10.3390/molecules26040803
|View full text |Cite
|
Sign up to set email alerts
|

Spin Hamiltonians in Magnets: Theories and Computations

Abstract: The effective spin Hamiltonian method has drawn considerable attention for its power to explain and predict magnetic properties in various intriguing materials. In this review, we summarize different types of interactions between spins (hereafter, spin interactions, for short) that may be used in effective spin Hamiltonians as well as the various methods of computing the interaction parameters. A detailed discussion about the merits and possible pitfalls of each technique of computing interaction parameters is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 164 publications
1
34
0
Order By: Relevance
“…However, our work showed that each kagomé layer of Cu 2+ ions consists of very-weakly interacting two-leg spin ladders, so the seemingly exotic magnetic properties previously attributed to magnetic frustration are simply explained by a well-studied S = 1/2 antiferromagnetic uniform Heisenberg chain model. To find a correct spin lattice for any given magnetic material, it is necessary to evaluate the relative strengths of various possible spin exchanges of a given magnetic system by using an unbiased and straightforward method such as the energy-mapping analysis, based on first principles DFT calculations [3,4,19,33].…”
Section: Discussionmentioning
confidence: 99%
“…However, our work showed that each kagomé layer of Cu 2+ ions consists of very-weakly interacting two-leg spin ladders, so the seemingly exotic magnetic properties previously attributed to magnetic frustration are simply explained by a well-studied S = 1/2 antiferromagnetic uniform Heisenberg chain model. To find a correct spin lattice for any given magnetic material, it is necessary to evaluate the relative strengths of various possible spin exchanges of a given magnetic system by using an unbiased and straightforward method such as the energy-mapping analysis, based on first principles DFT calculations [3,4,19,33].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the Dzyaloshinskii-Moriya and asymmetric spin exchanges, the energy-mapping analysis employs the four-state method [2,13], in which non-collinearly ordered broken-symmetry states are used. A further generalization of this energy-mapping method was developed to enable the evaluation of other energy terms that one might include in a model spin Hamiltonian [14].…”
Section: Energy Mappingmentioning
confidence: 99%
“…In this circumstance, there is a chance to stabilize a multiple-Q state by taking into account additional other interactions to the model in (1), such as the magnetic anisotropy [57,58,59,115,116,24,25,117], bond-dependent interactions in the form of compass and Kitaev type [118,119,120,121,122,123,124,125], and higher-order multiple-spin interactions derived by higher-order exchange processes beyond the Heisenberg one [126,127,60,128,129,130]. Also, thermal fluctuations [131,56,132], quantum fluctuations [133,134,135,136], and disorder by impurities [137,138,139,140,141] play a role in stabilizing such multiple-Q states.…”
Section: Frustration In Insulating Magnetsmentioning
confidence: 99%